Al Farabi’s Thoughts on Islamic Education Concepts: A Literature Review - Jusnira Paddiana; Juwita Saputri; Karin Yulfiarti; Zainul Arifin; Muhamad Jamil (Khalifa Journal of Islamic Education, 2021)
The concept of Islamic education according to medieval Islamic thinkers is always worth to be discussed. Each personality has holistic and dynamic ideas and styles of thinking that strongly influence and are successfully implemented in current Islamic educational institutions ranging from elementary school, middle school to university levels. This article will discuss the concept of Islamic education according to Muhammad ibn Tarkhan Abu Nasr al-Farabi, prominently known as Al-Farabi. This article was written using a qualitative method with an individual life history approach. All data were collected through al-Farabi's biographical book, the historical research literature on al-Farabi's, and supported by his phenomenal work. After the data is collected, the writer uses thematic analysis through content analysis to expose research findings. Overall, the results of the analysis conclude that there are five important aspects of al-Farabi's thoughts on Islamic education. These five aspects are i) the nature of the value of education, ii) teaching methodological approach, iii) teacher competence, iv) curriculum design, and v) learning evaluation model. This article can be used as a reference for Islamic educational institutions in designing Islamic education.